Algae as phycoremediation agent for municipal solid waste leachate at landfill area to create an istidamah and biah sihhiyyah - Mat Ali, Qurratu Aini; Othman, Rashidi; Hj. Baharuddin, Zainul Mukrim (Institut Terjemahan & Buku Malaysia Berhad, 2016)
Increasing urbanization and industrialization has caused the environment to deficient. One of the issues that closely related to the urban areas is the disposal of solid waste which occurred from human activities. Solid waste which disposed to the dustbin then will be transfer to the landfill as this method is the cheapest way to dispose the waste. Therefore, there are current technologies developed to remediate the landfill including the soil and water source at it surrounding that contaminated by leachate. Leachate is water that has penetrated through the solid waste and leached out some of the compound such as heavy metals and organic compounds to the underground soil or water. Phycoremediation is one of the ecological approaches which used plants and algae as the effective and environmental friendly method to regain or recover the contaminated soil and water. Algae have been identified as suitable agent for phycoremediation and have high potential with low-cost alternative for physicochemical treatments. Islam also strengthens the fact that in doing anything, moderate or balance (mizan) is very important in order to keep the earth sustainable (istidamah)with healthy environment (biah sihhiyyah) for future generation.